KONSTRUKSI BERITA KEKERASAN TERHADAP WARTAWAN DALAM PEMBERITAAN MAKASSAR TERKINI.ID (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
The issue related to journalist violence is seen by Makassar Terkini (terkini.id) as an act of lawlessness. Discriminatory treatment against journalists often occurs but has not received good handling from the authorities so that there is no deterrent effect for the perpetrators. Media Makassar Terkini (Terkini.id) in framing the news regarding the case of journalist violence that befell three journalists in the city of Makassar at the time of covering the RKUHP rejection action in front of the South Sulawesi DPRD office showed the side of the media in resolving cases which were deemed not fulfilling the portion of justice for victims who became exclusion of the malignancy of the police. This research is expected to provide benefits to the next generation and add insight into framing analysis, especially in the latest online media Makassar.